(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2026)
This article synthesizes key linguistic and clinical definitions, outlines practical diagnostic pathways suitable for primary care and school health services, and proposes prevention priorities for the Fergana context: early identification through school-based screening, menstrual health education, nutrition interventions targeting iron and iodine sufficiency, and timely referral for endocrine and gynecologic evaluation.